A case report and literature review on reactive cutaneous capillary endothelial proliferation induced by camrelizumab in a nasopharyngeal carcinoma patient - Lin, Yao; Lin, Yuxin; Zhong, Xiaoping; Chen, Qingshan; Tang, Shijie; Chen, Jiasheng (Frontiers in Oncology, 2023)
Camrelizumab, a monoclonal antibody, blocks programmed cell death protein-1 from binding to T cells and programmed cell death ligand 1 on tumor cells, thereby ensuring sustained T cell activation and blocking immune escape of various types of cancer, including nasopharyngeal carcinoma. Reactive cutaneous capillary endothelial hyperplasia (RCCEP) is the most common immune-related adverse event in patients treated with camrelizumab. We report a case nasopharyngeal carcinoma in a patient with camrelizumab-induced RCCEP. A 68-year-old man diagnosed with nasopharyngeal carcinoma developed RCCEP at multiple locations after 3 months of camrelizumab treatment. RCCEP of the right lower eyelid affected closure of the right eye. In this report, we also reviewed previous literature on camrelizumab-induced RCCEP. In summary, the mechanism underlying camrelizumab-induced RCCEP remains unclear. RCCEP typically gradually subsides after discontinuing camrelizumab treatment. Larger nodules can be treated with lasers, ligation, or surgery. Although surgical excision is effective, RCCEP may recur in patients undergoing camrelizumab treatment. RCCEP management may not be required in the absence of adverse effects on the patient’s daily life.